PENINGKATAN HASIL BELAJAR IPA DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI SEKOLAH DASAR - Selvia, Selvia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The results showed an increase. Improvement can be seen: a) learning implementation plan (RPP) obtained 73% (average) in the first cycle increased 93% (very good) in the second cycle, b) the implementation of aspects of teachers' first cycle 77% (Good) increased 89% (very good ) second cycle and aspects of students' first cycle 66% (average) increased 86% (very good) second cycle. c) student learning cycle I with 68.3 (moderately) increased 90.4 (excellent) second cycle. It can be concluded that learning science CTL approach can improve student learning outcomes Elementary School fourth grade El-Ma'arif West Pasaman. Kata Kunci: hasil belajar; IPA; pendekatan ctl